THE IMPACT OF POST-WELD HEAT TREATMENT ON RE-WELDING IN SHIELDED METAL ARC WELDING JOINT ST42 STEEL (Jurnal Teknologi (Sciences & Engineering), 2024)
Re-welding is a technique used to repair welds that are deemed defective and in danger of causing harm. Post-weld heat treatment is a method for improving welding-induced residual stresses, microstructural changes, hardness, and toughness. This work investigated the influence of post-weld heat treatment on the mechanical characteristics of ST 42 steel re-welding utilizing the SMAW technique and E6013 filler. Four samples with varying degrees of rewelding and post-welding treatment were analyzed. Based on the result, re-welding using SMAW to the St42 steel material led to a 20-40% decrease in mechanical properties, with the most significant reduction observed in the modulus of elasticity after two re-welding cycles. Conversely, post-weld heat treatment (PWHT) applied to the St42 steel subjected to two re-welding processes resulted in a 6-20% increase in mechanical properties, notably a 20% increase in the modulus of elasticity. These findings underscore the effectiveness of PWHT in enhancing mechanical properties, particularly microstructure recovery, in materials that have undergone re-welding.